In the Line of Fire : A Memoir - Musharraf, Pervez (London Pocket Books, 2008)
Heads of state almost never write memoirs while still in office, but Pakistani president Pervez Musharraf is no ordinary head of state. This is a political memoir like no other. Astonishingly candid, it reveals Musharraf's remarkable personal story as well as his key role in the war on terror.
Include Illustrations and Index.
Musharraf's Biography in English.
Keywords: Pakistan -- Politics and government -- Presidents -- Musharraf, Pervez